Male fertility and zygotic embryo germination in bananas - Luyiga, J. (Makerere University, 2022)
Crop improvement through crossbreeding relies on the generation of new hybrids from seeds. Therefore, seed set and seed germination are key determining factors for a successful breeding program. In banana breeding, both seed set and seed germination are low, especially in triploid and tetraploid bananas. To improve germination, embryos are extracted from seeds and cultured in vitro. Seed set is determined by the quantity and viability of pollen for the male parents, or male fertility, and by the receptibility of the female for the pollen, or female fertility. In this study, we tested the male fertility in terms of pollen quantity and viability of the main diploid genotypes (Calcutta 4, Malaccensis 250, TMB2x 7197-2, SH 3217, 10969S-1, Opp Zebrina, cv. Rose, TMB2x 5265-1, SH 3362, TMB2x 8075-7, Kokopo and TMB2x 9128-3) used as male donors of resistance to pest and disease resistance in banana breeding. Pollen quantity was determined by digital imaging and subsequent image analysis of pollen grains using imageJ software. Pollen viability was tested by soaking the pollens in 2,3,5- triphenyl tetrazolium chloride (TTC) stain followed by counting the stained pollen. We also investigated the optimal soaking time by soaking seeds in water for 0, 3, 5, 7, 9 days. The study utilized seeds obtained from 4x – 2x (1438K-1 – ITC0250 - malaccensis and 1201K-1 – 7197-2) and 2x – 2x (selfed ITC0249 - Calcutta 4 and selfed ITC1348 - Pisang Serun 404) crosses. The effect of hormones on the germination of banana embryos was also determined using 6-Benzylaminopurine (BAP) and Gibberellic acid (GA3) in vitro. Embryos were extracted and cultured on Murashige and Skoog media with 0.0, 0.5, and 1.0mg/l concentrations of BAP and GA3. The results indicated highly significant (p<0.001) difference among the genotypes for both pollen quantity and viability. Genotype and month interaction significantly (p<0.001) influenced both pollen quantity and viability. The pollen mean quantity was generally high in all genotypes ranging from 2588 to 28252 pollen grains per three anthers of a plant. The month influenced pollen quantity in SH 3217 and cv. Rose. Pollen viability (mean percentage) ranged from 42.69 to 99.67%. The genotypes less affected in terms of pollen viability were Calcutta 4, cv Rose, Kokopo, Opp Zebrina, SH 3362 and TMB2x 7197-2. Soaking seeds for 3 days significantly increased embryo germination success by 16.2% than in other tests. The addition of BAP and GA3 hormones into culture medium did not improve embryo growth but positively affected growth parameters in all genotypes. In conclusion, the observed differential responses in pollen quantity and viability for individual genotypes could be attributed to changes in physiological processes in order to cope with the constant fluctuations in the prevailing environmental conditions a term called genotypes by environment interactions. To improve banana embryo germination, the seeds should be soaked for 3 days before embryo extraction, and 1mg/l of BAP should be added to the embryo germination medium, not to improve germination, but to improve the growth of the plantlets after germination.